H
¯
(k) = [H
¯
i j
(k)]
n × n
with H
¯
i j
(k) = a
i j
H
i j
(k)
△ H
¯
(k) = [ △ H
¯
i j
(k)]
n × n
with △ H
¯
i j
(k) = a
i j
△ H
i j
(k)
N
¯
△
(k) = [N
¯
△ i j
(k)]
n × n
with N
¯
△ i j
(k) = a
i j
N
△ i j
(k)
L
¯
(k) = [L
¯
i j
(k)]
n × n
with L
¯
i j
(k) = a
i j
L
i j
(k)
Evidently, △ H
¯
(k) = M
¯
△
(k)F
¯
△
(k)N
¯
△
(k). Moreover, it is not
difficult to get that a
i j
= 0 if j ∉ 𝒩
i
. Defining
𝒲
p × q
≜ {V
~
= [V
i j
] ∈ ℝ
np × nq
| V
i j
∈ ℝ
p × q
, U
i j
= 0 if j ∉ 𝒩
i
}
(7)
Then, H
¯
(k)
and L
¯
(k)
are two sparse matrices which meet
H
¯
(k) ∈ 𝒲
n
x
× n
x
and L
¯
(k) ∈ 𝒲
n
x
× n
y
. It is worth pointing out that the
special structure of 𝒲
p × q
will be helpful to analysis and design of
the filter in Section 3. The more detailed information about this
structure can be found in the following lemma.
Lemma 1 [35]: Let P = diag{P
1
, P
2
, …, P
n
} and non-singular
matrix P
i
∈ ℝ
p × p
for all i = 1, 2, …, n. If X = PW for W ∈ ℝ
np × nq
,
then we can readily obtain W ∈ 𝒲
p × q
⟺ X ∈ 𝒲
p × q
.
Let
η(k) =
x
¯
T
(k) x
F
T
(k)
T
∈ ℝ
(2n) × n
x
,
υ(k) =
ω
T
(k) ξ
T
(k)
T
∈ ℝ
n
y
+ n
ω
,
z
¯
(k) = z
(k) − z
F
(k). Combining
the system (1) and distributed filter (5), one immediately obtains
the following augmented system:
η
(k + 1) = {A
η
(k) + θ(k)ΔA
η
(k)}η(k)
+
∑
s = 1
l
γ
¯
s
C
ηs
η(k − s) + D
1η
(k)υ(k)
+
∑
s = 1
l
γ
¯
s
D
2ηs
(k)υ(k − s) + E
η
(k) f (x(k))
+
∑
s = 0
l
γ
~
s
(k)[C
ηs
(k)η(k − s) + D
2ηs
(k)υ(k − s)]
z
¯
(k) = U
η
(k)η(k)
(8)
where
A
η
(k) =
A
¯
(k) 0
γ
¯
0
L
¯
(k)C
¯
(k) H
¯
(k) + △ H
¯
(k)
,
ΔA
η
(k) =
ΔA
¯
(k) 0
0 0
C
ηs
(k) =
0 0
L
¯
(k)C
¯
(k − s) 0
,
E
η
(k) =
E
¯
(k)
0
, D
1η
(k) =
B
¯
(k) 0
γ
¯
0
L
¯
(k)D
¯
(k) L
¯
(k)1
n
D
2ηs
(k) =
0 0
L
¯
(k)D
¯
(k − s) 0
, U
η
(k) =
U
¯
(k) −U
¯
(k)
Note that (8) is a p-periodic stochastic system. To be more
specific,
A
η
(k)
,
B
η
(k)
,
C
ηs
(k)
,
E
η
(k)
,
D
1η
(k)
,
D
2ηs
(k)
,
U
η
(k)
are all p-
periodic matrices.
Assumption 2 [36, 37]: If each function
f
i
( ⋅ ):ℝ → ℝ in (8) is
continuous and bounded, and there exist corresponding constant
scalars δ
i
and ρ
i
such that
f
i
(0) = 0 and
δ
i
≤
f
i
(α)
α
≤ ρ
i
, a ≠ 0, i = 1, 2, …, n
x
(9)
then, Υ
1
⩽ 0 and Υ
2
⩽ 0.
From Assumption 2 and [38], one can obtain
[ f
i
(x
i
(k)) − δ
i
x
i
(k)][ f
i
(x
i
(k)) − ρ
i
x
i
(k)] ≤ 0, i = 1, 2, …, n
x
(10)
Denote e
^
k
= [e
^
k1
, e
^
k2
, …, e
^
kn
x
]
T
∈ ℝ
n
x
as the unit column vector
where e
^
ki
equals to 1 when i = k and 0 otherwise. Then, we have
f (x(k))
x(k)
T
e
^
k
e
^
k
T
−
δ
i
+ ρ
i
2
e
^
k
e
^
k
T
∗ δ
i
ρ
i
e
^
k
e
^
k
T
f (x(k))
x(k)
≤ 0
(11)
Letting p-periodic matrices
Q(k) = diag{q
1
(k), q
2
(k), …, q
n
x
(k)} > 0, we have
f (x(k))
x(k)
T
Q(k) −F
2
Q(k)
∗ F
1
Q(k)
f (x(k))
x(k)
≤ 0
(12)
where
F
1
= diag{δ
1
ρ
1
, δ
2
ρ
2
, …, δ
n
x
ρ
n
x
},
F
2
= diag
δ
1
+ ρ
1
2
,
δ
2
+ ρ
2
2
, …,
δ
n
x
+ ρ
n
x
2
Furthermore, it follows from (12) that
f (x(k))
x
¯
(k)
T
Q(k) −1
n
T
⊗ (F
¯
2
Q(k))
∗ I
n
⊗ (F
¯
1
Q(k))
f (x(k))
x
¯
(k)
≤ 0
(13)
where F
¯
1
= (1/n)F
1
, F
¯
2
= (1/n)F
2
.
Remark 3: To ease the later derivation, we can get the following
inequality from (13). By adding this inequality to ΔV
1
(η(k)) and
ΔV
2
(η(k)), we can get (21)
ΔV
12
= −
f (x(k))
η(k)
T
Q(k) −1
n
T
⊗ (F
¯
2
Q(k)) 0
∗ I
n
⊗ (F
¯
1
Q(k)) 0
∗ ∗ 0
f (x(k))
η(k)
≥ 0
(14)
Before deducing our main results in this paper, we give the
following definitions and lemma.
Definition 1 [39]: System (8) is said to be stochastically stable if
for υ(k − s) ≡ 0 ( k ⩾ 0 and s = 0, 1, …, l) and any initial condition
η(0), the following inequality holds:
E
∑
k = 0
∞
∥ η(k) ∥
2
|η(0) < ∞
(15)
Definition 2: Given a disturbance attenuation level β > 0, for any
υ(k) ∈ l
2
[0, ∞) and T > 0, if the filtering error z
¯
(k) satisfies the
following dissipation inequality:
∑
i = 0
T
E z
¯
T
(i)𝒬z
¯
(i) + 2
∑
s = 0
l
z
¯
T
(i)𝒮υ(i − s) +
∑
s = 0
l
υ
T
(i − s)ℛυ(i − s)
⩾ β
∑
i = 0
T
E
∑
s = 0
l
υ
T
(i − s)υ(i − s)
(16)
under the zero-initial condition, then the system (8) is said to be
strictly (𝒬, 𝒮, ℛ)- β-dissipative.
Assumption 3: The dissipative coefficient matrices 𝒬 ⩽ 0,
ℛ = ℛ
T
.
Remark 4: In fact, define
υ
supply
(i) =
z
¯
T
(i) υ
T
(i) υ
T
(i − 1) ⋯ υ
T
(i − l)
T
. Then, the
supply rate [19, 40] in (16) can be expressed as
848 IET Control Theory Appl., 2017, Vol. 11 Iss. 6, pp. 846-856
© The Institution of Engineering and Technology 2017